Innovations in teacher education at the time of COVID19: an Australian perspective. Issue 4 (7th August 2020) - Scull, Janet; Phillips, Michael; Sharma, Umesh; Garnier, Kathryn
ABSTRACT: The university sector was hit hard by COVID-19 in early 2020 with global calls for universities to lockdown. The teacher education sector in most countries, including Australia, had not anticipated the shift to off-campus teaching of such a massive scale and the sector was not well prepared for the challenge. This paper reports how the Australian education sector responded to the COVID-19 pandemic and details how one Australian university implemented a number of innovations changing the mode of teaching and move to a fully online environment for all initial teacher education programmes. The innovations included the conversion of all face to face course work units into online units, including synchronous and asynchronous learning opportunities. The initial impact of the innovations on pre-service teachers was captured through systematic measures of engagement with the online content. Using these measures, we interviewed four academics who were identified as supporting high levels of interaction. We were keen to understand what contributed to fostering high levels of interaction of pre-service teachers. Key lessons learnt from the analysis are discussed with a hope that these practices might benefit others looking for ways to provide high-quality teacher education programmes during and after the COVID-19 pandemic.